(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2017)
This study aims to explicate the lexical meaning of minyak (oil) from the perspective of cognitive linguistics, as a symbol regularly used in Malay proverbs. The selection of the symbol has its roots in the belief that the noun has a close connection with the Malay culture with regards to its quality and usage.. Through the sub-corpus of proverbs sourced from www.malaycivilization.com which have been classified into specific categories, 84 proverbs related to minyak have been obtained and analyzed. The results of the analysis reveal that the Malay society is very creative in defining the meaning of minyak, ranging from the meaning associated with the domain [liquid] to an array of meanings of the domain [status], [attitude], [behaviour], [feeling] and [situation]. The extended meanings have acquired ameliorative (positive) or pejorative (negative) characteristics. The extension of the meanings confirm the creative nature of the Malay society in language use, as well as displaying the subtlety, sharpness and wisdom of the Malay mind, particularly in the selection of precise symbols to suit particular situations and circumstances. Keywords: proverbs, symbol, meaning, cognitive linguistics, ameliorative, pejorative